Numerical modelling of the snow flow characteristics surrounding Sanae IV Research Station, Antarctica - Beyers, Johannes Hendricus Meiring (Stellenbosch : University of Stellenbosch, 2011)
Thesis (PhD)--University of Stellenbosch, 2004.